The Effect of Self-Assessment System Justice Taxation, and Distrust of The Fiscus Party To The Act of Tax Evasion By The Taxpayer - Rubiatto Biettant; Miftah Syahdila; Charlie Charlie; Fahmi Alvin Maulana (Green Publisher Indonesia, 2023)
This study aims to examine the effect of the Self Assessment System, Tax Justice, Distrust of Tax Officers on the act of Tax evasion. The independent variables in this study are the Self Assessment System, Tax Justice, and Distrust of tax officials, while the dependent variable is the act of tax evasion. This study uses primary data by distributing questionnaires to taxpayers. 367 questionnaires have been distributed to taxpayers in the KPP Pratama Jakarta Gambir 4 area. The method used in this study is convenience sampling. Data analysis using multiple regression analysis data. The results of this study indicate that the Self Assessment System, Tax Justice has a negative effect on the act of tax evasion, while distrust of tax officials has a positive effect on the act of tax evasion. Based on the results of data analysis and discussions that have been carried out, it can be concluded that the self Assessment System does not have a significant negative effect on tax evasion actions